Importance économique du Port Autonome de Liège: rapport 2003 - Frédéric Lagneaux (National Bank of Belgium, 2005)
– The Port Autonome de Liège, with its 26 kilometres of berths and several multimodal platforms, plays an important role in the Walloon and Belgian economy. This update paper gives an extensive overview of the economic importance and the latest developments of the Port Autonome de Liège, through revised results for the period 1997 - 2003. Focusing on the three major variables of value added, employment and investment, it also provides some information about the financial situation of a few vital sectors. An indication concerning the financial health of the companies studied is also provided, using the National Bank's bankruptcy prediction model. In addition, it includes figures of several cargo traffics and draws a picture of social developments in the Port Autonome de Liège. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of these port activities are estimated in terms of value added (VA) and employment, on the basis of data from the National Accounts Institute. In the Liège harbour's network, direct VA came to 1 billion euro and total VA - the sum of direct and indirect VA - to 2 billion euro in 2003. In the same year direct and total employment respectively attained 12,400 and 28,500 fulltime equivalents, while investment directly linked with the port fell to 121 million euro. The position of the Port Autonome de Liège as the second largest inland port in Europe is threatened by the planned closure of the Cockerill Sambre's blast furnaces. This will take place gradually but will be completed by 2009. 2,700 direct and 4,500 indirect jobs are concerned, as well as 8 million tonnes of transhipment. However new spaces will be opened up, which means that new businesses will be created in the port area. New development sites are under construction and will soon be operative. An overall restructuring of the Liège harbour's network is under way and constitutes the main challenge for the Port Autonome de Liège's authorities in the next five years. In spite of this climate of uncertainty, the Port Autonome de Liège is striving to establish itself as a major logistic centre in the region, able to add value to the goods passing through it, in order to withstand the climate of increasing regional and international competition.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments.; Hafenentwicklung; Hinterland; Lüttich